2008
DOI: 10.1007/s00247-007-0741-5
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric renal leukemia: spectrum of CT imaging findings

Abstract: Renal leukemic involvement in children can present with a variety of CT imaging findings. Focal renal abnormalities as well as nephromegaly are frequently observed. Most commonly, renal leukemic involvement does not appear to impair renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 17 publications
4
34
0
2
Order By: Relevance
“…Patients with T-cell ALL and the M4 and M5 subtypes of acute myeloblastic leukemia are at a higher risk for extramedullary disease, including renal parenchymal involvement, which is the most frequent extramedullary metastatic site. 1 Consequences of leukemic infiltration of the kidneys are asymptomatic bilateral renal enlargement, acute renal failure, and/or secondary hypertension, as reported previously. We report a patient with end-stage renal disease (ESRD), receiving hemodialysis, and uncontrolled hypertension due to leukemic cell infiltration of the kidneys.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Patients with T-cell ALL and the M4 and M5 subtypes of acute myeloblastic leukemia are at a higher risk for extramedullary disease, including renal parenchymal involvement, which is the most frequent extramedullary metastatic site. 1 Consequences of leukemic infiltration of the kidneys are asymptomatic bilateral renal enlargement, acute renal failure, and/or secondary hypertension, as reported previously. We report a patient with end-stage renal disease (ESRD), receiving hemodialysis, and uncontrolled hypertension due to leukemic cell infiltration of the kidneys.…”
Section: Introductionsupporting
confidence: 59%
“…7 Multiple reports suggest that enlarged kidneys due to leukemic infiltration, detected by USG, CT, or excretory urography, is the most common imaging manifestation observed in renal involvement of ALL. 1 Olgar et al showed that renal leukemic infiltration is a risk-factor for developing hypertension, and they also determined that hypertension might be a risk factor for renal parenchymal disease. In that study, hypertension was found in 21 out of 334 (6.3%) patients with ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes leukemic infiltration of the kidneys is detected incidentally by imaging during the course of disease or during testing prior to treatment. Hilmes et al [7] retrospectively investigated 12 children with leukemia who were found to have renal leukemic involvement on contrast-enhanced abdominal CT. They detected focal renal parenchymal abnormalities, mostly bilateral and multifocal, more frequently than nephromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…4,22,129 Angiomyolipoma may occur sporadically, 22,131 although it is seen in up to 80% of patients with tuberous sclerosis (usually bilateral and/or multiple renal angiomyolipomas). [130][131][132] It can be also seen in von Hippel-Lindau syndrome, neurofibromatosis, 22 Sturge-Weber syndrome, autosomal dominant polycystic kidney disease, and pulmonary lymphangiomyomatosis. 133 Presentation at extrarenal sites such as in the liver, spleen, abdominal wall, retroperitoneum, lung, and genital region may also be seen.…”
Section: Benign Neoplasms Angiomyolipomamentioning
confidence: 99%
“…22,130,135 Imaging appearance varies considerably based on the amount and type of histologic elements present. Diagnosis can usually be made by CT or MRI that reveals macroscopic fat 131 ; however, fat is not pathognomonic or unique to angiomyolipoma and is occasionally seen in WT and RCC. 22 In fact, radiologic techniques using enhancement patterns and histogram analysis at CT and chemical shift MRI remain controversial to rule out RCC in histologically proven fat poor angiomyolipomas.…”
Section: Benign Neoplasms Angiomyolipomamentioning
confidence: 99%